Unstable angina: A rare presentation of minoxidil intoxication: A case report and literature review - Farzad Gheshlaghi; Shafeajafar Zoofaghari; Gholamali Dorooshi (Wolters Kluwer Medknow Publications, 2018)
Minoxidil is an antihypertensive direct vasodilator that can cause severe toxicity when sufficiently ingested. We report a case of accidental ingestion of 5 ml topical minoxidil solution 5% presented with chest pain and new-onset ST depressions. After giving IV saline and performing echocardiography/angiography, the patient fully recovered without any pharmacotherapy such as vasopressors and discharged 4 days after admission. The clinical toxicology, treatment, and previous case reports of minoxidil poisoning have been reviewed.